Registry Research Funding of the German Society of Plastic, Reconstructive and Aesthetic Surgeons (DGPRaC) and Research Funding Report 2019/2020 - Moellhoff, N.; Prantl, L.; Behr, B.; Beier, J. P.; Daigeler, A.; Dragu, A.; Eisenhardt, S. U.; Fuchs, P. C.; Germann, G.; Hirsch, T.; Horch, Raymund E.; Infanger, M.; et al. (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2020)
Zusammenfassung
CRIS-Team WoS Importer:2020-10-09